Preparation of umami octopeptide with recombined Escherichia coli: Feasibility and challenges. Issue 1 (1st January 2018) - Zhao, Liming; Zhang, Yin; Venkitasamy, Chandrasekar; Pan, Zhongli; Zhang, Longyi; Guo, Siya; Xiong, Wei; Xia, Hu; Wenlong, Liu; Xinhua, Gou
ABSTRACT: The taste of umami peptide H-Lys-Gly-Asp-Glu-Glu-Ser-Leu-Ala-OH (LGAGGSLA) is controversial. One possible reason for this controversy is the use of chemically synthesized LGAGGSLA to confirm its taste. To explore other ways to further confirm the flavor of LGAGGSLA, we developed a new strategy to prepare a bio-source peptide by adopting a gene engineering method to express LGAGGSLA in recombinant Escherichia coli . In our previous work, we structured the LGAGGSLA recombinant expression system and optimized the culturing conditions for preparing a fusion protein. However, the fusion protein was not cleaved by enterokinase to obtain LGAGGSLA. Because the cleavage conditions of commercial enterokinase were not specific and recombinant engineered bacteria had the potential to be used in industrial processes, in this addendum, we calculated the mass and volume yields of key processing steps in the preparation of LGAGGSLA, and established a model of cleavage conditions with the cleavage ratio of LGAGGSLA. When the LGAGGSLA was confirmed to show umami taste, it is considered as a new umami or umami enhancer. The gene information of LGAGGSLA should have a great potential in the development of new flavor product and food product containing high umami flavor.